2019
DOI: 10.3390/ijms20153730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Common Molecular Basis in Alzheimer’s and Parkinson’s Diseases

Abstract: Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the most common neurodegenerative disorders related to aging. Though several risk factors are shared between these two diseases, the exact relationship between them is still unknown. In this paper, we analyzed how these two diseases relate to each other from the genomic, epigenomic, and transcriptomic viewpoints. Using an extensive literature mining, we first accumulated the list of genes from major genome-wide association (GWAS) studies. Based on these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 133 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…H 2 S has been widely considered as a toxic gas in the scientific community for over 300 y, but understanding of this small molecule has changed since H 2 S is found to involve in the physiological and pathological mechanism of the brain [20]. SIRT1 was suggested to suppress the synuclein aggregate formation in PD and it was also correlated with H 2 S in neuronal senescence and diabetes [14,15,21]. Herein, this study aims to investigate the roles of H 2 S and SIRT1 in PD, and drew a conclusion that H 2 S ameliorated SIRT1 activity through acceleration of SIRT1 sulfhydration to increase the autophagy flux and attenuate damage of SH-SY5Y cells induced by MPP~+.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S has been widely considered as a toxic gas in the scientific community for over 300 y, but understanding of this small molecule has changed since H 2 S is found to involve in the physiological and pathological mechanism of the brain [20]. SIRT1 was suggested to suppress the synuclein aggregate formation in PD and it was also correlated with H 2 S in neuronal senescence and diabetes [14,15,21]. Herein, this study aims to investigate the roles of H 2 S and SIRT1 in PD, and drew a conclusion that H 2 S ameliorated SIRT1 activity through acceleration of SIRT1 sulfhydration to increase the autophagy flux and attenuate damage of SH-SY5Y cells induced by MPP~+.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genes mentioned below are APOE and TREM2 associated with AD; CD38 variants with AD and PD; and SYT4 with PD ( Chang et al, 2018 ; Jansen et al, 2019 ). In addition, genetic studies found the association of SIRT1 with PD and AD ( Zhang A. et al, 2012 ; Rana et al, 2019 ) and with SCZ ( Kishi et al, 2011 ). A similar strategy to select the genes associated with NDvD as SCZ and ASD.…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%
“…Moreover, low levels of SIRT1 are present in NDgD as AD and PD ( Lutz et al, 2014 ; Singh et al, 2017 ). In addition, genetic studies found the association of SIRT1 with PD and AD ( Zhang A. et al, 2012 ; Rana et al, 2019 ) and with SCZ ( Kishi et al, 2011 ).…”
Section: Genes Associated With Obesity and Neurodegenerative And Neurmentioning
confidence: 99%
“…In the second review [ 12 ], Rana et al analyzed how AD and PD could relate to each other from the genomic, epigenomic, and transcriptomic viewpoints since their relationship is still unidentified. AD is clinically characterized by a steady loss of memory and impairment of other cognitive functions such as communication, language inability, advanced visual processing, and movement [ 13 ].…”
mentioning
confidence: 99%
“…While the mutual pathological overlap may be linked to genes, mitochondrial dysfunction, neuroinflammation, tau protein, and α-synuclein protein [ 15 ], common risk factors are signified by oxidative stress, insufficiency of vitamin D, and aging [ 16 ]. In the present review [ 12 ], Rana et al first accumulated a list of genes from major genome-wide association (GWAS) studies by recurring to extensive literature mining. As a result of GWAS studies, the authors recovered only one gene (i.e., HLA-DRB5) shared between AD and PD that has been reported earlier several times for AD and PD, exhibiting a strong relationship with the CNS.…”
mentioning
confidence: 99%